Food security status and cardiometabolic health among pregnant women in the United States - Murkey, Jamie A.; Gaston, Symielle A.; Payne, Christopher W.; Jackson, W. Braxton; Jackson, Chandra L. (Frontiers in Global Women's Health, 2024)
Introduction Pregnant women and their offspring are particularly vulnerable to food insecurity and its adverse effects during critical periods of fetal development. Racially/ethnically minoritized women in the United States (US) who are pregnant are additionally burdened by food insecurity, which may exacerbate cardiovascular health (CVH) disparities. Despite heightened social vulnerability, few studies have employed an intersectional framework, including race and gender, to assess the food insecurity and CVH relationship. Methods We used 2012–2018 and 2020 National Health Interview Survey data among US pregnant women aged 18–49 years old (N = 1,999) to assess the prevalence of food insecurity status by race/ethnicity and to investigate household food security status in relation to ideal CVH, using a modified ideal CVH (mICVH) metric. We categorized food security status as “very low/low”, “marginal”, or “high”. To assess mICVH, a summary score of 7 clinical characteristics and health behaviors was dichotomized as yes [(7)] vs. no [<7]. Prevalence ratios (PRs) and 95% confidence intervals (CIs) of associations between food security status and mICVH were estimated using Poisson regression with robust variance. Models were adjusted for age, household income, educational attainment, geographic region, marital status, alcohol consumption, survey year, and race/ethnicity (in overall model). Results The mean age ± standard error was 29.0 ± 0.2 years. Among pregnant women, 12.7% reported “very low/low”, 10.6% reported “marginal”, and 76.7% reported “high” food security. “Very low/low” food security prevalence was higher among NH-Black (16.2%) and Hispanic/Latina (15.2%) pregnant women compared to NH-White (10.3%) and NH-Asian (3.2%) pregnant women. The mICVH prevalence was 11.6% overall and 14.5% for NH-White, 4.1% for NH-Black, 5.0% for Hispanic/Latina, and 26.7% for NH-Asian pregnant women. Among all pregnant women, “very low/low” and “marginal” vs. “high” food security status was associated with a lower prevalence of mICVH {[PRvery low/low = 0.26 (95% CI: 0.08–0.75)]; [PRmarginal = 0.47 (95% CI: 0.23 −0.96)]}. Conclusion Household food insecurity was higher among pregnant women in minoritized racial/ethnic groups and was associated with lower mICVH prevalence. Given the higher burden of food insecurity among minoritized racial/ethnic groups, food security may be an important intervention target to help address disparities in poor CVH among pregnant women.